An aesthetics of norm adherence: discourse and power in matrimonial and maraboutic relationships in Dakar - Moya, I (Anthropological Society of Oxford, 2022)
This article shows the homology between two hierarchical relationships defined by Islam: husband-wife and marabout-disciple. Wives and disciples ostentatiously declare their submission to the authority of their husbands or marabouts although these stereotyped statements are not directly related to reality. Such contradictions are the form of these relationships rather than a demonstration of power. What matters is the conformity of the discourse -and not the actions of people- to the principles that govern these relationships. In ethnographic as well as daily interactions, people strive to say what is the most ‘beautiful' and keep up appearances according to a moral system that values discretion and harmonious relations. The preservation of appearances and the ostentatious recognition of authority are not indexes of power relationships. Instead, they provide the ‘dominated' a form of autonomy within the framework of hierarchical relationships.